To validate and correlate radiologic grading of central and foraminal stenosis post-surgical decompression on degenerative lumbar canal stenosis - Niraj Narayan Singh; Kumar Rohit; Mahipal Ajitsinh Padhiyar (Asian Journal of Medical Sciences, 2024)
Background: Lumbar canal stenosis (LCS) is characterized as a narrowing of the canal diameter with age, which can lead to degenerative bone and soft-tissue changes. Aims and Objectives: The aim of the study is to validate the radiologic grading of central and foraminal through correlation with outcome after surgical decompression in degenerative LCS. Materials and Methods: A total of 23 patients with degenerative LCS who satisfied inclusion criteria and consented to participate in the study were selected and their Oswestry Disability Index (ODI) and Visual Analog Scale (VAS) for back and leg pain were recorded and their magnetic resonance imaging (MRI) was graded. Results: LCS is the reduction in the dimension of the central or lateral lumbar canal that occurs most frequently as a result of chronic degenerative changes at the lumbar motion segments. In our study, ODI has comparable improvement in all groups and it does not correlate with the severity of stenosis. However, VAS for leg pain has a greater prevalence in the shorter durations group (<60 months) which had an average of 8.0. If VAS for leg pain was more preoperatively, a better outcome was seen postoperatively. Conclusion: Decompression surgery for degenerative LCS shows significant improvement in ODI and VAS for back pain and leg pain irrespective of the severity of the stenosis by MRI grading or the severity of symptoms as assessed by VAS or ODI.